Nhận thức về hành vi tẩy xanh trong ngành mỹ phẩm: Vai trò điều tiết của tính xác thực xanh và tính minh bạch xanh - Nguyen Hong, Van; Nguyen Thi, Thao; Truong Nhat, Phuong; Nguyen Minh , Khanh; Nguyen Thi Thao, Van (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Employing a quantitative approach, the study analyzed data from 692 customers of green cosmetics companies through both online and offline survey platforms. The collected data were processed using reliability testing, measurement model analysis, second-order structural equation modeling (SEM), and moderation analysis via Smart PLS 4.0 software. The research findings highlight three key insights: (1) Consumer perceptions of greenwashing negatively affect green trust, thereby reducing their intention to purchase green products. (2) Green trust plays a mediating role in the relationship between greenwashing perception and intentions to purchase. (3) Green authenticity and green transparency serve as crucial moderating factors, significantly alleviating the negative impact of greenwashing perception on green trust and reinforcing the positive relationship between green trust and purchase intention. Based on these findings, recommendations and policy implications are provided for regulatory authorities, green cosmetics enterprises, and consumers.
Keywords: Consumer perception; Greenwashing; Green trust; Green purchase intention; Green transparency; Green authenticity